Pelatihan Daur Ulang Logam (Alumunium) bagi Masyarakat Karang Joang - Jatmoko Awali; Ika Ismail; Olivier Aryatama; Yunita Triana; Wentika Asih (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Metal recycling is an effective way to deal with the abundance of scrap metal such as drink can, scrap iron and others. Metal recycling skill is needed by the community especially in the youth to help reduce the amount of scrap metals in the environment and to develop a new creative and innovative industry, however the community doesn’t have the skills needed and have never gotten the training on metal recycling. Therefore, in the community service acticity of the Materials and Metalurgical Engineering Study Program, ITK, it was given metal recycling skill (aluminum) for the community. The metal recycling skill training was held in Kalimantan Institute of Technology campus, Balikpapan, East Kalimantan. The training was attended by 15 people from the community. The training was held by conducting presentation, practice, and discussion. The qualitative analysis results (from observation and discussion result) showed that all participant felt getting new knowledge and skill, that is the metal recycling skill.